EVALUATING THE IMPLEMENTATION OF DIFFERENTIATED INSTRUCTION IN ENGLISH LANGUAGE CLASSES - D’aquinaldo Stefanus Fani Seran; Nur Hidayanto Pancoro Setya Putro (Sanata Dharma University Yogyakarta, 2026)
This study aims to evaluate the suitability and effectiveness of the implementation of differentiated learning in English subjects, from the following aspects: student identification, learning objectives, socio-cultural, human resources (teachers and students), learning material planning, availability of facilities and infrastructure, utilization of facilities and learning processes, and outcomes after participating in learning. The methodology used was descriptive quantitative with a qualitative approach. The Context, Input, Process, Product (CIPP) evaluation model is used to evaluate it, while data collection was in the form of questionnaires, observations, document reviews, and interviews. The results of the study show the level of suitability and effectiveness of students: 76%, 82%, 77%, and 76%, while non-conformity or ineffectiveness: 24%, 18%, 23%, and 24%. This means that input, process, and output have not been implemented well. Meanwhile, for teachers: 83%, 84%, 86%, 84%, and inappropriate or ineffective: 17%, 16%, 14%, and 16%, which means it has been implemented well. The description above indicates positive results from differentiated learning in English. Teachers stated it was appropriate and effective, while students needed ongoing, specialized support to achieve shared expectations.